AMSERU - Samat, Noorasikin; Mohd Zaki, Hafizah Hanim; Manshor, Hanisah; Abd Malek, Mohamad Ashraff Danial; Ramli, Fatin Umaidah (2020)
The logo signifies the importance of research involving materials in order to facilitate and provide positive development among the Ummah. It consists of 3 circles highlighting the research scope of AMSERU itself. The shiny circle represents a persistent study in enlightening the community towards a positive scientific breakthrough of the research scope from time to time. The circle consisting of honeycomb shape represents the advanced materials. The circle consisting of earth within representing the green or renewable materials